The Feeling of Pleasure for Overweight Children during Different Types of Physical Activity - Aymen Hawani; Anis ben Chikha; Mohamed Abdelkader Souissi; Omar Trabelsi; Maher Mrayah; Nizar Souissi; Santo Marsigliante; Antonella Muscella (MDPI AG, 2023)
The feeling of pleasure during physical education (PE) could increase with physical activity participation and adherence for overweight children. While traditional games are known to have positive benefits on motor skill development, especially for children with poorer motor skills, and on the body mass of children, little is known about overweight children's feelings of enjoyment when playing these games. To identify a program of physical activity appreciated by overweight children, we tested the effect of different activities, namely soccer (SO), shot put (SP), and traditional motor games (TMGs), on the feelings of pleasure for 28 overweight male children (aged 12.11 ± 0.63 years, BMI 26.89 ± 0.15 kg·m−2) participating in a 3-month cross-over study. To measure affective responses to exercises, we applied a validated feeling scale. The data were collected during eight PE lessons, which were organized for each cycle taught. Post hoc pairwise comparisons revealed a significant difference (Z = −3.195, p < 0.01) between the mean feeling score reported after the SO cycle (2.48 ± 0.41) and that after the TMGs (3.04 ± 0.32). A similar significant difference (Z = −3.304, p < 0.01) was found between the mean feeling scores reported after the SP cycle (2.27 ± 0.32) and the TMGs (3.04 ± 0.32). There was no significant difference between the mean feeling scores reported after the SO (2.48 ± 0.41) and SP cycles (2.27 ± 0.32). In conclusion, the findings of the present study suggest that TMGs may have beneficial effects on the feelings of pleasure for overweight children. Therefore, TMGs might potentially be considered as an alternative to conventional physical activities.